Identification of inter-turn insulation faults in induction motor. Issue 2 (9th August 2019) - Venugopal, Gopu; Gopalakrishnan, V.; Rajkumar, S.P.
Abstract : Purpose: Induction motors (IMs) are considered one of the most important elements of the industrial process. However, in this environment, these machines are subject to electrical and mechanical faults, which may cause significant financial losses. Thus, the purpose of this paper is to propose an optimal identification of inter-turn insulation faults present in the random wound IM. Design/methodology/approach: The design approach deals with a simple technique, using the effect of the inter-turn fault in modifying the high-frequency components of the applied pulse-width-modulated voltage. Findings: The change in insulation strength between the turns affects the capacitive component of the stator line current. Resulting changes in wave shapes of the applied voltage have been studied with respect to both the distance of inter-turn faults from line end and reduction in the insulation strength, and hence in the insulation resistance value. Originality/value: Studies have been conducted by using computer simulation and validated by experiments. There is ample evidence that an impending and progressing inter-turn fault can be identified in adjustable speed drives driven by frequency converters by studying line-end coil-voltage waveforms.